2012
DOI: 10.1007/s00595-012-0331-5
|View full text |Cite
|
Sign up to set email alerts
|

Composite small cell and mucinous carcinoma originating from the intrahepatic bile duct: report of a case

Abstract: The biliary tract is a very rare site for the occurrence of extrapulmonary small cell carcinoma. A 68-year-old Japanese female was being followed up for autoimmune hepatitis, and was referred to our hospital because segmental intrahepatic bile duct dilation was found on routine imaging studies, suggesting intrahepatic cholangiocarcinoma. She underwent left lobectomy of the liver and concomitant resection of the caudate lobe. Microscopic examination of the explanted liver showed a primary composite tumor compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Furthermore, amphicrine tumours are thought to represent another phenotype of composite tumours and are characterised by the appearance of dual neuroendocrine and glandular features in the same cell. This type of tumour is extremely rare, with only a few such reports in the stomach, pancreas, and liver [ 4 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, amphicrine tumours are thought to represent another phenotype of composite tumours and are characterised by the appearance of dual neuroendocrine and glandular features in the same cell. This type of tumour is extremely rare, with only a few such reports in the stomach, pancreas, and liver [ 4 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Very rare cases of hepatocellular carcinomas can contain a small cell tumor component with neuroendocrine features, the HCC component expressing hepatocyte markers and AFP, and the SCC component reactive for chromogranin A and synaptophysin (Yamaguchi et al 2004;Garcia et al 2006;Yang et al 2009). Composite small cell and mucinous adenocarcinoma can also originate from intrahepatic bile ducts (see below; Ikegami et al 2013). Combined SCC and adenocarcinomas have been observed in the stomach (Jang et al 2007) and the colon (Scherwitz et al 2002) and found to have metastasized to the liver.…”
Section: Hepatic Pscc Mixed Typesmentioning
confidence: 99%
“…Histology and immunohistochemistry are the same as with small cell gallbladder carcinomas (Kuraoka et al 2003). Mucinous adenocarcinoma of intrahepatic bile ducts can rarely be combined with small carcinoma, the tumors showing CK 19-positive and chromogranin A-positive cell populations (Ikegami et al 2013). Small cell carcinoma of the bile ducts exhibits an aggressive biology (Jeon et al 2006), the longest reported survival after multidisciplinary management being 23 months (Okamura et al 2009).…”
Section: Small Cell Carcinoma Of the Bile Ductsmentioning
confidence: 99%